Pembentukan Negara Madinah dan Perkembangannya pada Aspek Sosial Politik Administrasi - Chalawa, Iqlima; Abida, Ni’ma Ummu; Anggitasari, Aulya Novi; Razaki, Khoirur; Amalia, Rosyida (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This article examines the formation of the Islamic state and civilization in Madinah following the hijrah of Prophet Muhammad (SAW) from Makkah, focusing on the social, political, and administrative dynamics that shaped the foundation of the early Muslim community. Through a literature-based study, Madinah formerly Yathrib is portrayed as a multicultural society consisting of the Aus and Khazraj tribes, who frequently engaged in conflict, alongside Muslim communities, Jews, hypocrites, and adherents of local beliefs. The hijrah is understood as a strategic moment that enabled the emergence of a new social order founded on justice, equality, and harmony. The Charter of Madinah is analyzed as the first constitutional document regulating inter-community relations while granting political legitimacy to the Prophet as a leader. Employing State Formation Theory and Ibn Khaldun’s concept of asabiyah, this study demonstrates that processes of group integration, establishment of authority, institutionalization of legitimacy, and law enforcement occurred systematically. The Prophet’s strategies in building the society such as forming brotherhood between the Muhajirin and Ansar, establishing the mosque as the center of communal life, promoting moral development, and organizing state administration in areas such as finance, law, and documentation are identified as crucial elements in the socio-political consolidation of Madinah.